Impact of Leadership Practices on Organizational Work Environments - Alkuwari , Ali Khamis M Z (Journal of Ecohumanism, 2025)
Leadership is increasingly being recognized as a significant aspect of organizational occupational safety. However, there are differences in describing how the leaders manage safety in the organization. This study examines the relationship between leadership styles, work engagement, and organizational support within the context of government agencies in Qatar. The present study incorporated different research designs, and the review was based on the published standard, namely PRISMA statement (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). This study has considered 21 related studies using Web of Science (WOS) and Scopus as the primary databases for this systematic literature review. Findings indicate that both leadership styles significantly impact work engagement, while organizational support plays a critical role in motivating employees and fostering a productive work environment. This systematic literature review also provides several limitations and recommendations for future direction.